Structure and expression of the PHO80 gene of Saccharomyces cerevisiae. - Madden, S L (1988)
In yeast, the repression of acid phosphatase under high phosphate growth conditions requires the trans-acting factor PHO80. We have determined the DNA sequence of the PHO80 gene and found that it encodes a protein of 293 amino acids. The expression of the PHO80 gene, as measured by Northern analysis and level of a PHO80-LacZ fusion protein is independent of the level of phosphate in the growth medium. Disruption of the PHO80 gene is a non-lethal event and causes a derepressed phenotype, with acid phosphatase levels which are 3-4 fold higher than the level found in derepressed wild type cells. Furthermore, over-expression of the PHO80 gene causes a reduction in the level of acid phosphatase produced under derepressed growth conditions. Finally, we have cloned, localized and sequenced a temperature-sensitive allele of PHO80 and found the phenotype to be due to T to C transition causing a substitution of a Ser for a Leu at amino acid 163 in the protein product.